The “Martyr of the Homeland”: The political construction of Cipriano Barata by the exalted liberal press (1829-1833) (Ágora Journal, 2024)
This article aims to examine the image of Cipriano Barata constructed by the exalted liberal press of Rio de Janeiro during the crisis of the First Reign and the beginning of the Regency period (1829-1833). In this study, we highlight the adaptations of European liberalism from the first half of the 19th century to the Brazilian reality. From this adaptation, we perceive the unique case of the exalted liberals as a political group that went against the tide of its time. By following the imprisonment process of Cipriano Barata, we understand to what extent the exalted liberal press defended its leader. In our research, we used the search tool of the digital newspaper library of the National Library, from which we traced periodicals that at some point mentioned Cipriano Barata during our time frame, where our interpretations were guided by notions and meanings of terms from dictionaries of the period.
Keywords: Cipriano Barata; liberalism; press; exalteds.